Automated Folding of Origami Lattices: From Nanopatterned Sheets to Stiff Meta‐Biomaterials. Issue 3 (20th November 2022) - van Manen, Teunis; Ganjian, Mahya; Modaresifar, Khashayar; Fratila‐Apachitei, Lidy E.; Zadpoor, Amir A.
Abstract: Folding nanopatterned flat sheets into complex 3D structures enables the fabrication of meta‐biomaterials that combine a rationally designed 3D architecture with nanoscale surface features. Self‐folding is an attractive approach for realizing such materials. However, self‐folded lattices are generally too compliant as there is an inherent competition between ease‐of‐folding requirements and final load‐bearing characteristics. Inspired by sheet metal forming, an alternative route is proposed for the fabrication of origamilattices. This 'automated‐folding' approach allows for the introduction of sharp folds into thick metal sheets, thereby enhancing their stiffness. The first time realization of automatically folded origami lattices with bone‐mimicking mechanical properties is demonstrated. The proposed approach is highly scalable given that the unit cells making up the meta‐biomaterial can be arbitrarily large in number and small in dimensions. To demonstrate the scalability and versatility of the proposed approach, it is fabricated origamilattices with > 100 unit cells, lattices with unit cells as small as 1.25 mm, and auxetic lattices. The nanopatterned the surface of the sheets prior to folding. Protected by a thin coating layer, these nanoscale features remained intact during the folding process. It is found that the nanopatterned folded specimens exhibits significantly increased mineralization as compared to their non‐patterned counterparts. Abstract : Functionalized metamaterials can serve as a platform for bone tissue regeneration. Inspired by sheet metal forming, an automated folding technique is developed and the folding of stiff miniaturized lattice structures from nanopatterned flat sheets is shown. The presented folding technique is highly scalable both in unit‐cell dimension as well as number of unit‐cells.